An Intriguing Endoscopic Case of Asymptomatic Crohn's Disease - Mena Boules MD; Ilyssa O. Gordon MD, PhD; Brian Kirsh MD; Maged K. Rizk MD (SAGE Publishing, 2013)
We present the case of a 64-year old male with Crohn's disease, who has intriguing endoscopic findings. Upon initial diagnosis at age 20, he received steroid therapy, but has not required any further medical intervention. He has remained relatively asymptomatic and keeps a healthy lifestyle. At routine colonoscopy, we identified pseudopolyps as well as tissue bridges within the colon, giving an unusual "swiss cheese" appearance. This case exemplifies the heterogeneity of Crohn's disease, emphasizing the possibility of finding evidence of ongoing disease despite lack of symptoms.